Pèlerinages barrésiens - Bompaire-Evesque, Claire (Quêtes littéraires, 2013)
This article is a inquiry about how Barrès (1862-1923) handles the religious rite of pilgrimage. Barrès stages in his writings three successive forms of pilgrimage, revealing what is sacred to him at different times. The pilgrimage to a museum or to the birthplace of an artist is typical for the egotism and the humanism of the young Barrès, expressed in the Cult of the Self (1888-1891). After his conversion to nationalism, Barrès tries to unite the sons of France and to instill in them a solemn reverence for “the earth and the dead” ; for that purpose he encourages in French Amities (1903) pilgrimages to historical places of national importance (battlefields; birthplace of Joan of Arc), building what Nora later called the Realms of Memory. The third stage of Barrès’ intellectual evolution is exemplified by The Sacred Hill (1913). In this book the writer celebrates the places where “the Spirit blows”, and proves open to a large scale of spiritual forces, reaching back to paganism and forward to integrative syncretism, which aims at unifying “the entire realm of the sacred”.